Bioevaluation and Targeted Modification of Temporin-FL From the Skin Secretion of Dark-Spotted Frog (Pelophylax nigromaculatus) - Wang, Wenjie; Yang, Wanqing; Du, Shouying; Xi, Xinping; Ma, Chengbang; Wang, Lei; Zhou, Mei; Chen, Tianbao (Frontiers in Molecular Biosciences, 2021)
Bioactive proteins secreted by the granular glands of amphibian skin play a self-defensive role, and exhibit various bioactivities in vitro and in vivo. In light of the severity of the problem of antibiotic resistance for treating infections, many antimicrobial peptides (AMPs) have been developed and applied in clinical microbial treatments. We identified a naturally derived and potent antimicrobial peptide, temporin-FL, obtained from the skin secretion of Pelophylax nigromaculatus via “shotgun” cloning. Two truncated analogues of this peptide were chemically synthesized to explore their structural-functional relationships. The results of a functional evaluation showed that all of the tested AMPs were active against gram-positive bacteria and fungi and demonstrated antibiofilm activity against methicillin-resistant Staphylococcus aureus (MRSA) but did not have an effect on gram-negative bacteria. Moreover, temporin-FLa demonstrated a higher level of hydrophobicity and enhanced antimicrobial efficiency, as well as hemolytic activity and cell cytotoxicity than the parent peptide. Temporin-FLb, which evidenced significantly less α-helicity, was less potent against various microbes but exhibited lower cytotoxicity relating to mammalian cells. Both of the synthesized analogues possessed a higher therapeutic index than the original peptide. Moreover, the membrane permeability assay and the measuring membrane depolarization assay declared that temporin-FL and its analogues induced membrane fracture and depolarization; the quantitative biofilm formation assay and the observations of MRSA biofilms using scanning electron microscopy revealed that the AMPs caused biofilm disruption and blocked biofilm formation, the former experiments all confirming their antimicrobial and antibiofilm properties. Hence, the optimization of temporin-FL offers insights for the discovery of new drugs for treating MRSA infections.